Fully Textured, Production‐Line Compatible Monolithic Perovskite/Silicon Tandem Solar Cells Approaching 29% Efficiency. Issue 40 (4th September 2022) - Mao, Lin; Yang, Tian; Zhang, Hao; Shi, Jianhua; Hu, Yuchao; Zeng, Peng; Li, Faming; Gong, Jue; Fang, Xiaoyu; Sun, Yinqing; Liu, Xiaochun; Du, Junlin; et al.
Abstract: Perovskite/silicon tandem solar cells are promising avenues for achieving high‐performance photovoltaics with low costs. However, the highest certified efficiency of perovskite/silicon tandem devices based on economically matured silicon heterojunction technology (SHJ) with fully textured wafer is only 25.2% due to incompatibility between the limitation of fabrication technology which is not compatible with the production‐line silicon wafer. Here, a molecular‐level nanotechnology is developed by designing NiOx /2PACz ([2‐(9H‐carbazol‐9‐yl) ethyl]phosphonic acid) as an ultrathin hybrid hole transport layer (HTL) above indium tin oxide (ITO) recombination junction, to serve as a vital pivot for achieving a conformal deposition of high‐quality perovskite layer on top. The NiOx interlayer facilitates a uniform self‐assembly of 2PACz molecules onto the fully textured surface, thus avoiding direct contact between ITO and perovskite top‐cell for a minimal shunt loss. As a result of such interfacial engineering, the fully textured perovskite/silicon tandem cells obtain a certified efficiency of 28.84% on a 1.2‐cm 2 masked area, which is the highest performance to date based on the fully textured, production‐line compatible SHJ. This work advances commercially promising photovoltaics with high performance and low costs by adopting a meticulously designed HTL/perovskite interface. Abstract : An ultrathin hybrid hole transporting layer employing NiOx /[2‐(9H‐carbazol‐9‐yl) ethyl]phosphonic acid enables complete and uniform coverage on fully textured indium tin oxide (ITO)/silicon surface with pyramid structures of 2–5 µm sizes. As a result of the depleted shunt pathways between ITO and perovskite top cell, a certified record efficiency—28.84%—is achieved on perovskite/silicon tandem solar cells with fully textured, production‐line compatible bottom silicon wafers.